Dynamics of Ukrainians’ Perceptions of National Symbols as a Reflection of Resistance to Russian Aggression - Sliusarevskyi , Mykola (Insight: the psychological dimensions of society, 2025)
The purpose is to investigate the changes that have been taking place during the full-scale Russian invasion in the perceptions of Ukrainian society about national symbols and may be of interest in terms of assessing its psycho-emotional state, prospects for further social development, preservation, and restoration of citizens’ mental health and personal growth. Methods. The dynamics of Ukrainians’ symbolic representations have been tracked in the course of monitoring, which has been carried out since the 2000s under the author’s leadership in all regions of the country, except for the temporarily occupied territories, since 2015. The monitoring is carried out through mass surveys, based on a sample representing the adult population of Ukraine aged 18 and older. About 1200 respondents were interviewed at each monitoring stage. The list of symbolic objects discussed in the article contained about 20 items. Results. The first of the surveys conducted after the full-scale Russian invasion showed that the external armed aggression initially led to a reduction of the symbolic consciousness of Ukrainian society to military-patriotic, mostly military content limited to the challenges of war. However, in the third year of the full-scale war, reliable data were obtained that indicated the regeneration and expanded reproduction of Ukrainians’ symbolic consciousness. Along with an increased focus on situationally determined military content, the frequency of choosing symbols related to the actualization of historical memory and artistic and aesthetic feelings of citizens has increased. Their symbolic preferences have become not only more unanimous but also much more diverse and richer in content. Discussion and Conclusions. The hypothesis that in the context of a full-scale Russian invasion, the leading role of Ukraine-centered symbols in the symbolic preferences of Ukrainians would further increase was fully confirmed. Other hypotheses were also confirmed: the increase in the number of national symbols in response to an existential threat to the nation, the actualization of the Ukrainian citizens’ historical memory as a factor in the further transformation of their symbolic representations, and the acquisition of transregional unity by the national symbolic space. However, the confirmation of these hypotheses has been delayed. Therefore, it is reasonable to assume that the identified psychological effects of reduction, regeneration, and expanded reproduction of symbolic consciousness may fit into the more general hypothesis of simplification/complication in the national community’s structure of perceptions about their nation’s symbols in the face of events threatening its existence. It also seems legitimate to assume that the observed regeneration and expanded reproduction of symbolic preferences indicate that Ukrainian citizens are gradually recovering from the psychological shock caused by the war, increasing their adaptive potential and ability for post-traumatic growth. The author considers the acquisition of transre- gional unity a sign of a new quality of Ukrainians’ symbolic consciousness. However, this process is hampered by the territorial localization of historical memory.